Which of the following correctly simplifies the expression 2 to the power of 3 multiplied by 3 to the power of 0 whole over 5, t
he whole squared.? (5 points) 2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 1 squared over 5 squared. = 64 over 25.
2 to the power of 3 multiplied by 1 whole over 5, the whole squared. = 2 to the power of 5 multiplied by 1 squared over 5 cubed. = 32 over 125.
2 to the power of 3 multiplied by 0 whole over 5, the whole squared. = 2 to the power of 6 multiplied by 0 over 5 squared. = 0
2 to the power of 3 multiplied by 0 whole over 5, the whole squared. = 2 to the power of 5 multiplied by 0 over 5 cubed. = 0
Hello! Your answer was 19! There is no possible way for me to show you how to work this out using base ten blocks! Hopefully you can work it out in your head next time! :)